Legal safeguards for juvenile accused at trial stage - Al-shahrani, Maha Saad Said (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to analyze and compare the legal guarantees of the juvenile accused in the trial stage under both the Saudi regime and the Convention on the Rights of the Child. On the analytical and comparative approach, through the analysis of criminal legal texts dealing with the organization of legal safeguards for the juvenile accused at the trial stage until we find out their adequacy and inadequacy and their effectiveness in achieving a fair trial for juveniles, and compare them with the Convention on the Rights of the Child to address deficiencies and deficiencies, if any, and rectify them. This study culminates in a number of results, the most important of which are: The conviction of the juvenile should not be considered a priority, because it is unfair to load the juvenile mistakes in his juvenile period, in addition to this may affect the future of the event, and make him an adult deviant. The study also reached a number of recommendations, the most important of which are the following: Using the technical means in the social observation house and the girls’ welfare institution when conducting the trial with juveniles, because of its importance in the event feeling of peace and comfort Consequences of being in a room isolated from the atmosphere of the trial.